2021
DOI: 10.33417/tsh.748139
|View full text |Cite
|
Sign up to set email alerts
|

Orduda Sosyal Hizmet: Terör Gazilerinin Depresyon ve Yaşam Doyumunun Değerlendirilmesi

Abstract: Bu çalışma terör gazilerinin sosyo-demografik özellikleri, depresyon ve yaşam doyumu düzeyleri arasındaki ilişkiyi incelemeyi amaçlamaktadır. Araştırmada nicel araştırma tasarımından yararlanılmıştır. Araştırmanın örneklemini terörle mücadelede aktif olarak rol alarak eve dönüş yapmış 225 terör gazisi oluşturmaktadır. Veri toplama aracı olarak araştırmacı tarafından hazırlanmış yarı-yapılandırılmış sosyo-demografik form, Diener ve arkadaşları (1985) tarafından geliştirilmiş yaşam doyumu ölçeği ve Beck ve arkad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 45 publications
0
9
0
4
Order By: Relevance
“…For example, Duran and Unsal (2014) did not find a significant relationship between resilience and depression scores and explained this situation by the fact that Veterans had a strong family support. It is emphasized that family support increases the quality of life (Bascillar, 2017). In line with this finding, Aciksoz (2011) revealed that the support from family members was important for Veterans in terms of meeting their basic needs and helping them to cope with stress.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…For example, Duran and Unsal (2014) did not find a significant relationship between resilience and depression scores and explained this situation by the fact that Veterans had a strong family support. It is emphasized that family support increases the quality of life (Bascillar, 2017). In line with this finding, Aciksoz (2011) revealed that the support from family members was important for Veterans in terms of meeting their basic needs and helping them to cope with stress.…”
Section: Introductionmentioning
confidence: 66%
“…The majority of studies mostly employed quantitative methodologies and scales adapted from different cultures. Previous research examined PTSD, depression, and anxiety (Guloglu, 2016;Karairmak & Guloglu, 2014;Keten et al, 2014), as well as the phenomenon of veteranism in terms of variables such as social relations, economic status, resilience, selfesteem, and quality of life (Bascillar, 2017;Duran & Unsal, 2014;Oznur, 2013). Two previous qualitative studies examined the experience of Turkish Veterans with disabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu durumda çocuğun ikametgâhını belirleyen; bakımı, eğitimi, Türkiye'den politik katılım yoluyla müracaatçılar lehine olumlu gelişmeler yaşanmasına neden olan örneklerden biri de malul sayılmayan gazilerle ilgili yapılan çalışmadır. Gaziler sosyal hizmetin müracaatçı grupları arasında yer almaktadır ve sosyal hizmet mesleği gazilerin iyilik hallerinin sağlanmasında önemli işlevler üstlenmektedir (Başcıllar & Karataş, 2021). Türkiye'de terörle mücadele sırasında yaralanan ve beden bütünlüğü bozulan ancak mevzuattaki boşluk nedeniyle gazi sayılmayan kişiler "malul sayılmayan gazi" olarak tanımlanmaktadır.…”
Section: Poli̇ti̇k Sosyal Hi̇zmetunclassified
“…Sosyal hizmet uzmanının eğiticilik rolü ise müracaatçıların hak ve yükümlülükleri, başvuru yapılacak makamlar, kurumların işleyişleri, kurumlar arası ilişkiler ve prosedürler hakkında müracaatçıların bilgilendirilmesini sağlamaktır. Bu nedenle alanda çalışan sosyal hizmet uzmanlarının gazi ve aile üyelerine sunulan hizmetler, sivil toplum örgütlerinin işlevleri, yapı ve mevzuata hakim olması gerekmektedir (Başcıllar, 2021).…”
Section: Gaziler Ve Orduda Sosyal Hizmet Uygulamalarıunclassified